THE EFFECT OF PHYSICAL EXERCISES IN TERMS OF THE (LUMP) TABLE ON DEVELOPING THE PHYSICAL PROFICIENCY OF ADVANCED FOOTBALL PLAYERS - Assist. Prof. Dr. Abdullah Mohammed Tatawy; Adnan Mohammed Shnawa (Galaxy International Interdisciplinary Research Journal, 2023)
The problem of the study is represented in that the players’ performance during matches regarding certain technical and planning aspects does not elevate to the high level despite the fact that these players play in the premier league and possess a good skill level. This has led the researchers to guess that the players’ physical proficiency is not at the required level. This is confirmed by conducting the physical proficiency test for the players. They found it as (42), which in turn is considered a weak estimate for the premier league players of the advanced class. Therefore, the researchers have decided to prepare physical exercises in terms of the (Lump) table, wondering whether these exercises have an effect on the level of physical proficiency for the advanced football players.